Egoistic versus Prosocial Decision Making: an Eye Movement Data Report - Anastasia Peshkovskaya (Scientific Data)
Abstract Eye tracking data are highly promising in revealing novel and valuable evidence on human behavior and decision making. Data descripted in this article were collected in fourteen experiments with SMI eye tracking glasses in individual and social decision making conditions. The dataset is available on Harvard Dataverse and include data of 14 subjects with 4,180 visual behavior metrics summary and 3,744 eye moment records in decision-related areas of attention. Data may be applicable in computational models of oculomotor activity to explain decision process and predict its outcomes.